Uterine transplantation in an era of successful childbirths from living and deceased donor uteri: Current challenges - Roman Chmel; Zlatko Pastor; Jan Matecha; Libor Janousek; Marta Novackova; Jiri Fronek (Biomedical Papers, 2020)
Background and Aims. Uterine transplantation (UTx) is an experimental sterility treatment method in women with absolute uterine factor infertility. This article describes the current trends and risks in UTx and provides an overview of our experience with this method, to date. Methods: Based on our experience with the Czech UTx trial and the published results of other trials, we describe the possibilities and risks of this perspective method in the treatment of absolute uterine factor infertility (AUFI). Results: Twelve healthy babies were born in 2014-2018 after more than 40 uterine transplantations. There is no general consensus whether it is more suitable to transplant uteri from living or deceased donors, and nulliparous or parous women (with proven obstetrical functionality). Most centers prefer to collect at least ten frozen embryos from in vitro fertilization (IVF) cycles before transplantation. The serious complication of a surgically successful uterine transplantation is posttransplant partial stenosis of the uterine-vaginal anastomosis that may be a technical problem for embryo transfer, outflow of menstrual blood, and sexual satisfaction due to the narrowed and shortened vagina. This paper concludes that, currently, procurement of the uterus and the transplant procedure are surgically feasible and that none of the transplanted uteri have been lost due to rejection but only because of graft thrombosis or infection. Conclusion: Uterine transplantation, after optimization of surgical methods, selection of suitable donors, standardization of immunosuppressive therapy, adjustment of assisted reproductive technologies and obstetrical proceedings might be an effective therapeutic method for women with AUFI who wish to have their own biological child.